Characterization of mAb dimers reveals predominant dimer forms common in therapeutic mAbs. Issue 5 (3rd July 2016) - Plath, Friederike; Ringler, Philippe; Graff-Meyer, Alexandra; Stahlberg, Henning; Lauer, Matthias E.; Rufer, Arne C.; Graewert, Melissa A.; Svergun, Dmitri; Gellermann, Gerald; Finkler, Christof; Stracke, Jan O.; Koulov, Atanas; et al.
ABSTRACT: The formation of undesired high molecular weight species such as dimers is an important quality attribute for therapeutic monoclonal antibody formulations. Therefore, the thorough understanding of mAb dimerization and the detailed characterization mAb dimers is of great interest for future pharmaceutical development of therapeutic antibodies. In this work, we focused on the analyses of different mAb dimers regarding size, surface properties, chemical identity, overall structure and localization of possible dimerization sites. Dimer fractions of different mAbs were isolated to a satisfactory purity from bulk material and revealed 2 predominant overall structures, namely elongated and compact dimer forms. The elongated dimers displayed one dimerization site involving the tip of the Fab domain. Depending on the stress applied, these elongated dimers are connected either covalently or non-covalently. In contrast, the compact dimers exhibited non-covalent association. Several interaction points were detected for the compact dimers involving the hinge region or the base of the Fab domain. These results indicate that mAb dimer fractions are rather complex and may contain more than one kind of dimer. Nevertheless, the overall appearance of mAb dimers suggests the existence of 2 predominant dimeric structures, elongated and compact, which are commonly present in preparations of therapeutic mAbs.